A general strategy towards superhydrophobic self-cleaning and anti-corrosion metallic surfaces : an example with aluminum alloy - Zheng, Shunli (2021)
Corrosion and contamination of metallic structures can cause loss of their functionality as well as aesthetic values. In this study, we describe a general strategy to prepare superhydrophobic self-cleaning and anti-corrosion surfaces for metallic structures. As a specific example, a superhy-drophobic coating (SHC) on aluminum alloy was prepared by a simple etching combined with the decoration of a low-surface-energy material. The optimal SHC has a water contact angle (CA) at ~157.4◦ and a sliding angle (SA) of ~8.3◦ due to the synergy of binary hierarchical structures and chemical modification. The SHC showed low adhesion to dry contaminants and a series of liquids, displaying a good self-cleaning effect. The SHC maintained superhydrophobicity after exposure to air and humid condition at 60◦C for 7 days. In addition, the electrochemical measurements reveal that the anti-corrosion performance was enhanced by reducing the corrosion current density (Jcorr) by 1 order of magnitude and increasing the corrosion potential (Ecorr) by 0.527 V as compared to the bare Al alloy substrate after immersion for 168 h.